Determinants of Bilateral Trade Flows - SRIVASTAVA, Rajendra Kumar (Institutional Knowledge at Singapore Management University, 1986)
What factors influence the level of trade flows that occur between nations? Past studies have answered this question primarily in terms of distance and economic size. The present study considers additional variables as potential determinants of trade relations between nations. Also, trade flows are analyzed by the type of products being exported and imported. The findings show that several additional variables are significant determinants of the level of bilateral trade relations between nations. In addition, it is found that models of trade flows are more appropriate for manufactured goods than they are for basic commodities.